2019
DOI: 10.1029/2018ja026131
|View full text |Cite
|
Sign up to set email alerts
|

First MMS Observation of Energetic Particles Trapped in High‐Latitude Magnetic Field Depressions

Abstract: We present a case study of the Magnetospheric Multiscale (MMS) observations of the Southern Hemispheric dayside magnetospheric boundaries under southward interplanetary magnetic field direction with strong By component. During this event MMS encountered several magnetic field depressions characterized by enhanced plasma beta and high fluxes of high‐energy electrons and ions at the dusk sector of the southern cusp region that resemble previous Cluster and Polar observations of cusp diamagnetic cavities. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 55 publications
(81 reference statements)
4
41
0
Order By: Relevance
“…These counterstreaming populations form even when the reconnection in the two hemispheres is not simultaneous (Fuselier et al, 2014). Alternatively, the counterstreaming O + populations could form through the process described in Nykyri et al (2019) when the IMF had a large B Y component. Assuming these velocities are constant and assuming a field line length of 10 R E , ionospheric ions take~5-10 min to propagate to the subsolar region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These counterstreaming populations form even when the reconnection in the two hemispheres is not simultaneous (Fuselier et al, 2014). Alternatively, the counterstreaming O + populations could form through the process described in Nykyri et al (2019) when the IMF had a large B Y component. Assuming these velocities are constant and assuming a field line length of 10 R E , ionospheric ions take~5-10 min to propagate to the subsolar region.…”
Section: Discussionmentioning
confidence: 99%
“…In this event, a sustained interval of northward IMF mass loads the boundary layer through the aforementioned process. Although the MMS orbit does not go into the cusp proper, the spacecraft occasionally observe cusp-like cavities at midlatitudes away from the subsolar region (Nykyri et al, 2019). Although very high O + densities are observed in the boundary layer and the magnetospheric ion source rivals that in the magnetosheath, reconnection is still observed at the low-latitude magnetopause after the IMF rotates southward.…”
Section: 1029/2019gl082384mentioning
confidence: 99%
See 2 more Smart Citations
“…Cluster observations revealed 90° pitch angle electrons in the cavity, strongly suggestive of a local acceleration mechanism (Nykyri et al., 2012; Walsh et al., 2010). Recently, MMS observation suggested that low‐latitude component reconnection can also trigger similar structure near the cusp region (Nykyri et al., 2019).…”
Section: Introductionmentioning
confidence: 99%